ANALYSIS OF MOTIVATION, LEADERSHIP AND TRAINING ON THE PERFORMANCE OF LECTURERS AND STAFF STIE TRISNA NEGARA BELITANG - Helisia Margahana (International Journal of Economics, Business and Accounting Research (IJEBAR), 2019)
This study aims to determine and explain the effect of both simultaneously and partially on motivation, leadership and job training on the performance of STIE Trisna Negara staff and lecturers. This study used a quantitative descriptive research design. The population is 74 lecturers and staff, STIE Trisna Negara. The total sample is 44 respondents. The sampling technique used a purposive sampling method. The questionnaire was used to collect data. The data analysis technique used is statistical analysis. The results showed that the F test of motivation, leadership and job training simultaneously and significantly affected the performance of lecturers and employees of STIE Trisna Negara. The results of the t test indicate that motivation has a positive and significant effect on the performance of lecturers and employees of STIE Trisna Negara. Leadership has a positive and significant effect on the performance of lecturers and staff of STIE Trisna Negara. Training has a positive and significant effect on the performance of lecturers and staff of STIE Trisna Negara. The results of the coefficient of determination show that motivation, leadership and training have an effect of 59.1% on the performance variables of STIE Trisna Negara lecturers and staff. The most dominant influence on the performance of lecturers and staff of STIE Trisna Negara is the leadership variable because it has the highest t-count value, namely 3.305. Keywords: Performance, Motivation, Leadership, Training